Handy Book / Nur Fadhilah Rosian … [et al.] - Rosian, Nur Fadhilah; Mohd Rawi, Faeizah; Ahmad, Siti Shafiyah; Yaakob, Siti Saffanah; Shaffei, Siti Nur Fadhilah; Hasnan, Nurul Hani; Ahmad, Noor Kamariah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Handy Book of manual regarding UiTM Kampus Bandaraya Melaka's education system is created to help new students especially for those who came from Sabah and Sarawak. Other than that, this manual is also provides other benefit to students as well as their parents such as this manual provide the exact location of UiTM Kampus Bandaraya Melaka, facilities provided and others. The existence of this manual is essential to help the new student to know better about UiTM Kampus Bandaraya Melaka surroundings. This manual will be created with a full colour version in order to make it interesting and in a small of size to make it convenience to the user. This is the first time introduced in UiTM Kampus Bandaraya Melaka. The manual will be posted to the students who accept the UiTM Kampus Bandaraya Melaka's offer in further their studies.